Predictors of scaffold failure and impact of optimized scaffold implantation technique on outcome: Results from the German-Austrian ABSORB RegIstRy - Boeder, Niklas F.; Kastner, Johannes; Mehilli, Julinda; Muenzel, Thomas; Naber, Christoph; Neumann, Till; Richardt, Gert; Schmermund, Axel; Woehrle, Jochen; Zahn, Ralf; Riemer, Thomas; Achenbach, Stephan; et al. (Catheterization and Cardiovascular Interventions, 2021)
Aims We aimed to investigate predictors of scaffold failure and the potential impact of an optimized scaffold implantation technique by means of a learning curve on long-term clinical outcome after bioresorbable scaffold (BRS) implantation and to evaluate predictors of scaffold failure.
CRIS-Team WoS Importer:2021-07-02